Management of mealybug (Drosicha stebbingi) in poplar based agroforestry in Bilaspur, Uttar Pradesh - Dhiman, R.C.; Gandhi, J.N. (Indian Journal of Agroforestry, 2020)
Moderate to heavy infestation of mealybug (Drosicha stebbingi) was recorded on poplar plantations in Bilaspur (Rampur), U.P. during 2012. Mealybug population was monitored in two different plantations of 1.4 years and 2.4 years age. Mealybug population was counted and the trees were divided into six categories based on the intensity of insect infestation viz., I0-No infestation, I1-Scattered infestation on trees, I2-Severe infestation on lower half ofthe crown, I3-Over 50 nymphs on the main stem, I4-Over 50 nymphs on atleast one branch of the tree and I5-Severe infestation on the entire tree. Six insecticidal treatments viz., CS0=No spray, CS1-carbofuran 0.3%, CS2-acephate 75WP, CS3- chloropyriphos 20 EC, CS4-cypermethrin 5%, CS5-monochrotophos 36% SL were applied for testing their efficacy to manage the insect population. The insect count was recorded 10 days after the treatments. The average insect population before sprays was 78.48 nymphs/tree on two years old trees having an average height of 8.3 m and average dbh of 7.47 cm, whereas its average number on one year old trees with 5.3 m average height and 4.40 cm dbh before spray was 47.29/tree. The insect population significantly declined after the treatment. The D. stebbingi population was recorded 2.33/tree for 1.4 years old and 7.06/tree for 2.4 years old plantations. Acephate and chloropyriphos sprays proved effective in managing the insect population.